The development of Soviet society : plan and performance - Ed. John G. Eriksen. Associate ed. Robert Farrell. (The Institute for the Study of the USSR)
Papers grown from a conference held in Munich in October 1966 under the auspices of the Institute for the Study of the USSR.Includes bibliographical references.